El caso de una vivienda como revelación formal para una posible revitalización del centro histórico de Riobamba, caso 1 - Jiménez Carrillo, David Rodrigo (2022)
Considering the attempt of the historic center of Riobamba to adapt to the development of commercial activities or services, which shows a residential reduction caused by people's preferences to build their homes outside the city and keep their property in the historic center as a source of income, there are problems ranging from insecurity outside working hours to the abandonment of patrimonial properties, destruction or incoherent interventions that alter the conception of the historic center; The present research is based on the need for a proposal that aims at the revitalization of the historic center through the recovery of a house with patrimonial value, a space of opportunity as a model to find the necessary formal response for an intervention. The housing is selected based on an analysis of the historical events that occurred in the historical development of the city as a tool to help find patterns of reorganization of the activities of the time, possible areas of study and the property respectively, the latter through valuation criteria for feasible buildings for modifications that can be made without compromising their formal characteristics. The block is analyzed as the area was studied, its pre-existences and mainly aspects of form, function and technology of the selected housing, which allows identifying potential elements for intervention, such as the participation of a second patrimonial property because of its unique location, so a proposal beyond the selected housing itself is proposed, which articulates the two heritage properties plus two large empty spaces left by destroyed old houses, together dynamize four flows within the block to develop necessary activities in the historic center.